The Digitalisation of Social Entrepreneurship: Development and Practical Implications from a Bibliometric Perspective - Argatu, Ruxandra; Vavura, Nicolae Marius (Technium Social Sciences Journal, 2025)
Technological development stands as a buzzword, enabling sustained welfare in various areas, particularly for entrepreneurial ventures. Digital instruments allow entrepreneurs to be in touch with market changes and be one step ahead of competition, reducing physical barriers and connecting bits of information through a single click. To stand apart in a digitally evolving landscape, organisations must prove they are digitally mature, have willingness towards digital transformation, and that they display a supportive organisational culture which drives long-term change. Apart from the economic implications, digitalisation is a key pillar of the 2030 Agenda for Sustainable Development, nurturing sustainable social progress and assisting social entrepreneurship in its ambitious, transformational pursuits. Through digitalisation, the functioning of social enterprises and their interaction with their stakeholders are significantly reshaped, hence producing valuable social outcomes. By employing bibliometric analysis through specific search queries operated in the Clarivate (Web of Science) and Scopus databases, the paper aims to identify the most recent developments in the research concerning the digitalisation of social enterprises, to establish future research directions. The findings reveal increasing research interest for the digitalisation of social entrepreneurship and its rapid development into practical directions such as social value creation, management, and dynamic capabilities. There also seems to be a geographic polarisation trend, that may possibly indicate different general approaches or schools of thought concerning social enterprise digitalisation, reinforced by the distinctive historical economic progress of the UK and US versus Europe and their influence on South-East Asia and Middle East respectively.